'Ein dürftiger Stoff': Hermann and the Failure of German Liberation Opera (1815–1848). Issue 2 (24th September 2018) - van Kooten, Kasper
Abstract : This article traces the development of national opera on political-historical themes in Germany between 1815 and 1848 and attempts to explain why this genre ultimately did not succeed. The focus will lie on the warrior hero Arminius/Hermann, one of the most potent national symbols of the nineteenth century, who was indeed brought to the German opera stage, but could never conquer it. The period between 1815 and 1848 not only forms a crucial phase in the coming of age of German opera against the background of a burgeoning national conscience, but also presents a lacuna in the current literature on Arminius as an opera character. Two early nineteenth-century Arminius opera projects will be discussed: musical realizations of August von Kotzebue's 1813 libretto Hermann und Thusnelde and French composer Hippolyte Chélard's 1835 opera Die Hermannschlacht, based on a libretto by Carl Weichselbaumer. Questions of authorship, patronage, musical style and reception will be addressed. This article presents a history of an operatic 'misfit' that fills a hiatus in the study of German nineteenth-century opera and will add to our understanding of the peculiar relation between opera and German national thought during the first half of the century.